Rhabdomyolysis due to Trimethoprim-Sulfamethoxazole Administration following a Hematopoietic Stem Cell Transplant. (18th October 2015) - Augustyn, Alexander; Lisa Alattar, Mona; Naina, Harris
Abstract : Rhabdomyolysis, a syndrome of muscle necrosis, is a life-threatening event. Here we describe the case of a patient with chronic myeloid leukemia who underwent a haploidentical stem cell transplant and subsequently developed rhabdomyolysis after beginning trimethoprim-sulfamethoxazole (TMP/SMX) prophylaxis therapy. Rechallenge with TMP/SMX resulted in a repeat episode of rhabdomyolysis and confirmed the association. Withdrawal of TMP/SMX led to sustained normalization of creatine kinase levels in the patient. A high index of suspicion is necessary to identify TMP/SMX as the cause of rhabdomyolysis in immunocompromised patients.